Notícias do abismo: Mário de Sá-Carneiro e A Confissão de Lúcio - Eiras, Pedro (2012)
In A confissão de Lúcio (Lúcio's Confession, 1914), Mário de Sá-Carneiro places all of his characters on a precise scale: at the bottom is the despicable bourgeoisie; at the top is the artist, whose characteristics cannot be articulated. Ricardo, Lúcio and Gervásio oscillate between these points; they are the "something in the middle". Although no one character can avoid being evaluated according to this hierarchy, nonetheless each character must invent a means of escape - the continuation of himself in the other. In short, he must write himself other - or even sacrifice writing for the superior experience of silence.